Respuesta :
Answer:
The second term is -6 , the fourth term is 0 , the eleventh term is 21
Step-by-step explanation:
* Lets revise the explicit formula
- An explicit formula will create a sequence using n, the number
position of each term.
- If you can find an explicit formula for a sequence, you will be able
to quickly and easily find any term in the sequence by replacing
n with the number of the term you want
- It defines the sequence as a formula in terms of n.
* Now lets solve the problem
- The formula of the sequence is A(n) = -9 + (n - 1)(3)
- A(n) is any term in the sequence
- n is the position of the number
- To find the second term put n = 2
∵ n = 2
∴ A(2) = -9 + (2 - 1)(3) = -9 + (1)(3) = -9 + 3 = -6
* The second term is -6
- To find the fourth term put n = 4
∵ n = 4
∴ A(4) = -9 + (4 - 1)(3) = -9 + (3)(3) = -9 + 9 = 0
* The fourth term is 0
- To find the eleventh term put n = 11
∵ n = 11
∴ A(11) = -9 + (11 - 1)(3) = -9 + (10)(3) = -9 + 30 = 21
* The eleventh term is 21
Answer:
Second term = -6
Fourth term = 0
Eleventh term = 21
Step-by-step explanation:
We are given the following explicit formula of an arithmetic sequence and we are to find the second, fourth and the eleventh terms of this sequence:
[tex]a_n=-9+(n-1)(3)[/tex]
where [tex]a_n[/tex] = nth term, [tex]a_1=-9[/tex] and [tex]n[/tex] = number of term.
Second term [tex](a_2) = -9+(2-1)(3)[/tex] = -6
Fourth term [tex](a_4) = -9+(4-1)(3)[/tex] = 0
Eleventh term [tex](a_{11}) = -9+(11-1)(3)[/tex] = 21